Pathomorphology of severe grade 3-4 hepatic encephalopathy in decompensated cirrhosis patients with acute-on-chronic liver failure - Shulyatnikova, T. V.; Tumanskyi, V. O.; Tumanska, L. M.; Шулятнікова, Тетяна Володимирівна; Туманський, Валерій Олексійович; Туманська, Любов Михайлівна (My University, 2024)
The study was aimed to determine of the most significant pathomorphological signs of severe hepatic encephalopathy (HE) in deceased cirrhotic patients with acute-on-chronic liver failure (ACLF) syndrome based on changes of the glioneuronal complex and the level of tissue ammonia. Using pathohistological, histochemical, and immunohistochemical methods, the cerebral cortex, thalamus, striatum, and cerebellum of 21 deceased patients with acutely decompensated liver cirrhosis with ACLF syndrome and HE Grade 3-4 were examined in comparison with control group, which included 30 deceased patients from acute cardiovascular failure. The study revealed that during HE Grade 3-4 as a component of ACLF, in all studied brain regions, there was a reliably (p<0.05) higher histochemical level of tissue ammonia (up to 500%), increased numbers (up to 215.69%) of apoptotic neurons (according to caspase-3), reduced (up to 119.60%) level of synaptophysin, increased expression of glutamine synthetase (up to 253.02%) and aquaporin-4 (up to 481.81%) associated by reduced (up to 296.81%) expression of glial fibrillary acidic protein in astrocytes, increased (up to 11-fold) numbers of Alzheimer type 2- astrocytes, expansion of perivascular and pericellular «edematous» spaces (up to 890.81%), increased numbers of amyloid bodies (up to 5-fold), increased area of immunopositive material of CD68+ microgliocytes (up to 114.78%) with an increase (up to 71.91%) in the proportion of CD68+ amoeboid microglia. The above-mentioned changes confirm that the loss of consciousness and other psychoneurological manifestations of severe HE Grade 3-4 are due to compound ammoniaassociated changes in the components of the glioneuronal complex, namely: adaptive remodeling and dystrophic changes in astrocytes, reduced synaptic transmission and apoptotic neuronal death, reactive changes in microglia with a small proportion of microgliocytes involved in phagocytosis, cytotoxic brain edema and dysfunction of the glymphatic system. Дослідження присвячене визначенню найбільш суттєвих патоморфологічних ознак тяжкої печінкової енцефалопатії (ПЕ) у померлих хворих на цироз печінки з синдромом гострої на тлі хронічної печінкової недостатності (ГХПечН) на підставі змін гліонейронального комплексу та рівня тканинного аміаку. За допомогою патогістологічних, гістохімічних, імуногістохімічних методів досліджено кору великих півкуль головного мозку (ГМ), таламус, смугасте тіло, мозочок 21 померлого хворого на гостро декомпенсований цироз печінки із синдромом ГХПечН та ПЕ Grade 3-4 в порівнянні з групою контролю, що включила з 30 померлих від гострої серцево-судинної недостатності пацієнтів без ПЕ. Результати дослідження показали, що при ПЕ 3- 4 ступенів тяжкості в складі синдрому ГХПечН з у всіх досліджених відділах ГМ виявляється достовірно (p<0,05) і значно вищий (до 500%) рівень тканинного аміаку, підвищена кількість (до 215,69%) апоптотичних нейронів (за каспазою-3) та знижений (до 119,60%) рівень експресії синаптофізину, підвищений (до 253,02%) рівень експресії глютамінсинтетази і аквапорину-4 (до 481,81%) та знижений (до 296.81%) рівень експресії гліофібрилярного білку в астроцитах, підвищена (до 11 разів) кількість астроцитів Альцгеймера 2 типу, значне (до 890,81%) розширення периваскулярних і перицелюлярних «набрякових» просторів, підвищена (до 5 разів) кількість амілоїдних тілець, підвищена (до 114,78%) площа експресії CD68+ мікрогліоцитів та збільшена (до 71,91%) частка CD68+ амебоїдних мікрогліоцитів. Отримані дані свідчать про те, що зниження свідомості та інші психоневрологічні прояви тяжкої ПЕ 3-4 ступенів тяжкості зумовлені аміак-асоційованими морфо- функціональними змінами гліонейронального комплексу, а саме: адаптивним ремоделюванням та дистро- фічними змінами астроцитів, зниженням синаптичної передачі та апоптозом нейронів, реактивними змінами мікроглії з незначним зростанням частки фагоцитуючих мікрогліоцитів, а також цитотоксичним набряком ГМ та дисфункцією глімфатичної системи.
Патоморфологія 3-4 ступенів тяжкості печінкової енцефалопатії у хворих на декомпенсований цироз печінки з синдромом гострої на тлі хронічної печінкової недостатності
Keywords: hepatic encephalopathy; liver cirrhosis; neuropathology; immunohistochemistry; ammonia; Alzheimer type 2 astrocytes; ameboid microglia; amyloid bodies; печінкова енцефалопатія; цироз печінки; патоморфологія; імуногістохімія; аміак; астроцити Альцгеймера 2 типу; амебоїдна мікроглія; амілоїдні тільця